THE DETERMINANTS OF HOUSEHOLD CONSUMPTION PATTERNS IN KLANG VALLEY - Al Sarah Alyaa Al Buhari,; Kamisah Supian,; Sharifah Hilmi Syed Abdullah,; Sara Shakira Shari, (Journal of Islamic, Social, Economics and Development, 2023)
People are having difficulty obtaining necessities due to the worrying state of the economy. Household consumption patterns have been the centre of an individual's spending behaviour study in improving an individual's financial planning. The decision of a household over how much to spend or save is a microeconomic issue because it pertains to the individual units of the economy. The research study's main goals were to suggest the dimensions of household spending patterns. A pilot test study was conducted during Matta Fair 2022 at PWTC, Kuala Lumpur. The Statistical Package for the Social Sciences (SPSS) 27.0 is employed to identify the relationships between consumption expenditure and household budgeting in improving household consumption patterns. Data are mainly quantitative, where descriptive statistics were conducted to analyze the data. The results of the study demonstrate a substantial relationship between consumption expenditure and household budgeting is significantly related to household consumption patterns. According to this research, a family should practice financial planning and be conscious of developing saving habits rather than spending more money on unnecessary things. Individuals must control their spending behaviour to lead a great and peaceful life.